The Effect of ICT-based Classwide Peer Tutoring (CWPT) Application and Motivation to Biology Education Student Creativity in ICT Learning - Evita Anggereini; Retni S Budiarti; M Erick Sanjaya (BIODIK, 2018)
Abstract. The rapid development of ICT, especially in learning, could not be parted from ICT intervention. Many benefits obtained from ICT developments, if this technology is utilized optimally in learning, there will have an impact on improving the quality of learning in particular and the quality of education in general. The lack of student knowledge and motivation for ICT technology can have an impact on students' creativity in using this technology optimally in learning. Peer tutoring can be an alternative solution to this problem. Peers who have more understanding and skill in using existing applications in ICT can be empowered to overcome these problems. Peer Tutoring type Classwide Peer Tutoring (CWPT) will be able to help students who are lacking in knowledge, understanding, skills and creativity. The aim of this study is to find out the influence of the application of ICT-based Classwide Peer Tutoring (CWPT) and Motivation towards the creativity of Biology education students in ICT learning.This research is an experimental study with a 2x2 factorial design. The independent variable in the form of experimental treatment, namely: Peer Tutoring strategy consisting 2 factors, namely CWPT and conventional type, while for attribute variables namely motivation, also consists of 2 factors, namely: high motivation and low motivation. Both of these independent variables will be examined for their influence on the dependent variable, namely student creativity in ICT learning. The population is 6th semester biology education students and the sample was taken by Total Sampling technique. The data analysis technique uses descriptive data analysis and inferential statistics of 2-ways ANOVA.The results of the study show that 1. There is no effect of the CWPT model on student creativity. 2. There is a motivational influence on student creativity in learning ICT. 3. There is no interaction between the model and the motivation to learn ICT with student creativity. Thus, the role of motivation is very large in influencing student creativity. Keywords: Classwide Peer Tutoring (CWPT) model, motivation, creativity Abstrak. Perkembangan ICT yang begitu pesat, dunia pendidikan khususnya dalam pembelajaran juga tidak luput dari intervensi ICT ini. Banyak manfaat yang diperoleh dari perkembangan ICT yang kalau teknologi ini dimanfaatkan secara maksimal dalam pembelajaran maka akan berdampak pada peningkatan kualitas pembelajaran khususnya dan mutu pendidikan umumnya. Kurangnya pengetahuan mahasiswa dan motivasi mahasiswa akan teknologi ICT ini dapat membawa dampak terhadap kreatifitas mahasiswa dalam menggunakan teknologi ini secara maksimal dalam pembelajaran padahal banyak manfaat yang dapat diperoleh dari teknologi ini.Peer Tutoring dapat menjadi alternatif pemecahan masalahnya. Teman sebaya yang memiliki pemahaman yang lebih dan terampil dalam menggunakan aplikasi yang ada dalam teknologi ICT ini dapat diberdayakan untuk mengatasi permasalahan tersebut. Peer Tutoring tipe Classwide Peer Tutoring(CWPT) akan dapat membantu mahasiswa yang rendah pengetahuan, pemahaman, skill dan kreativitasnya. Tujuan pene;itian ini adalah untuk mengetahui pengaruh penerapan Classwide Peer Tutoring (CWPT) berbasis ICT dan Motivasi terhadap kreativitas mahasiswa pendidikan Biologi dalam pembelajaran ICT. Penelitian ini merupakan penelitian eksperimen dengan desain faktorial 2x2. Variabel bebas berupa perlakuan eksperimen yaitu: strategi Peer Tutoring yang terdiri dari 2 faktor yaitu tipe CWPT dan tipe konvensional, sementara untuk variabel atribut yaitu motivasi juga terdiri dari 2 faktor yaitu: motivasi tinggi dan motivasi rendah. Kedua variabel bebas ini akan diteliti pengaruhnya terhadap variabel terikatnya (variabel dependent) yaitu kreativitas mahasiswa dalam pembelajaran ICT. Populasinya mahasiswa pendidikan biologi semester 6 dan sampelnya diambil dengan teknik Total Sampling. Teknik analisis datanya dengan menggunakan analisis data deskriptif dan statistik inferensial anava 2 arah. Hasil penelitian memperlihatkan bahwa 1. tidak terdapat pengaruh model CWPT terhadap kreativitas mahasiswa. 2. Terdapat pengaruh motivasi terhadap kreativitas mahasiswa dalam belajar ICT. 3. Tidak terdapat interaksi antara model dengan motivasi belajar ICT siswa dengan kreatifitas mahasiswa. Dengan demikian peranan motivasi sangat besar sekali dalam mempengaruhi kreatifitas mahasiswa. Kata kunci: Model Classwide Peer Tutoring (CWPT), motivasi, kreativitas